Novel Screen Printed Flexible Magnetoelectric Thin Film Sensor. (2016) - Chlaihawi, A.A.; Emamian, S.; Narakathu, B.B.; Ali, M.M.; Maddipatla, D.; Bazuin, B.J.; Atashbar, M.Z.
Abstract: A novel screen printed and flexible magnetoelectric (ME) thin film sensor was developed for the detection of AC magnetic fields, at room temperature. The ME sensor was fabricated by screen printing piezoelectric based polyvinylidene fluoride (PVDF) ink on flexible and magnetic Metglas ® substrate. Silver (Ag), as top electrode, was then deposited on the printed PVDF layer using bar coating technique. The performance of the fabricated device was investigated by measuring the induced voltage response towards varying AC magnetic fields and frequencies. An electromechanical resonance of 50 kHz, with a maximum voltage of 21.1 mV, was obtained for the induced voltage-frequency dependence measurements. A linear relationship with a sensitivity of 503.3 V/T and correlation coefficient of 0.9994 was also obtained towards varying AC magnetic fields.